Wikipedia = Heterotopia. Issue 4 (2nd October 2021) - Flavin, Michael
ABSTRACT: This paper analyses the online encyclopaedia Wikipedia using Michel Foucault's (1926–1984) concept of heterotopia. In Foucault's writings, heterotopias are both similar to and distinct from the conditions that give rise to them. The paper undertakes a case study of one entry on Wikipedia (the entry for the "Episteme") focusing primarily on the main entry and the talk page. The methodology is content analysis with a directed approach: data were gathered in November–December 2020. The paper argues Wikipedia can usefully be analysed as a heterotopia because it exposes the contentious conditions of knowledge production, which is not standard practice for an encyclopaedia. The article adds to our understanding by applying the Foucauldian concept of heterotopia to a specific Wikipedia entry, highlighting how knowledge is produced out of dispute and subjective discourses.